2022
DOI: 10.21203/rs.3.rs-2099833/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence of high-risk Human papillomavirus infections and associated factors among women living with HIV in Shashemene town public health facility, Southern Ethiopia

Abstract: Background: Every year, large number of women are suffering from cervical cancer. Particularly women living with HIV are at high-risk of being suffered with it. Early testing of high-risk HPV infection can significantly reduce the incidence of cervical cancer. However, lack of early and regular testing has been identified as one of the major problems among risky populations. Methods: Institutional-based cross-sectional study design was conducted among women living with HIV in Shashemene town public health faci… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
2
4
0
Order By: Relevance
“…Our study revealed that 42.6% (95% CI = 33-52.6%) of WLWHIV were tested positive for Hr-HPV. These findings align with results from several studies conducted across Africa, including Cameroon (46.43%) [27], Botswana (40.4%) [28], South Africa (36.7%) [29], Uganda (45%) [30], Zimbabwe (43%) [31], and Southern Ethiopia (35.2%) [32]. However, a study in Ghana reported a lower frequency of 14.5% [33].…”
Section: Discussionsupporting
confidence: 88%
“…Our study revealed that 42.6% (95% CI = 33-52.6%) of WLWHIV were tested positive for Hr-HPV. These findings align with results from several studies conducted across Africa, including Cameroon (46.43%) [27], Botswana (40.4%) [28], South Africa (36.7%) [29], Uganda (45%) [30], Zimbabwe (43%) [31], and Southern Ethiopia (35.2%) [32]. However, a study in Ghana reported a lower frequency of 14.5% [33].…”
Section: Discussionsupporting
confidence: 88%
“…About seventy-four (22.1%) study participant women responded that they had a previous history of STI other than HPV, of which 32 (43.2%) were founded to be HPV positive. Hence the prevalence of HPV among study participants who had a previous history of STI was much higher than those study participants who did not have a previous history of STI (43.2% vs 5.0%), This nding was in line with reports from Shashemene, southern Ethiopia (20), Ethiopian Public health institute, Addis Ababa (7). A signi cant statical association was observed between a previous history of STI and HPV infection (AOR=14.43, 95%CI=6.31-32.99, P=0.001).…”
Section: Discussionsupporting
confidence: 88%
“…So the prevalence of HPV infection among HIV-positive women was much higher than those of HIV-negative women (20.3% vs 7.3%). This nding was supported by studies in Shashemene, southern Ethiopia (20), Nigeria (21), in Amazonas (22), in Tanzanian (23). There was a signi cant statical association between HIV infection and HPV prevalence (AOR=3.53,95%CI=1.46-8.54, P=0.005).…”
Section: Discussionmentioning
confidence: 52%
“…This finding is supported by studies conducted in the Amhara regional state and northwest Ethiopia 9,22 . The possible reason for this might be due to HPV infection is more prevalent in individuals with STIs and different STIs can facilitate HPV virus transmission 32,33 . Therefore, women having other STIs in addition to HIV should be checked for precancerous cervical lesions.…”
Section: Discussionmentioning
confidence: 58%
“…Studies carried undertaken in the southwest, 23 northwest, 22 and south of Ethiopia 35 corroborate this finding. Unprotected sexual contact is one way that HPV can spread from one person to another, which may account for the higher risk of HPV among women who have multiple sexual partners 32 . Therefore, in addition to counseling women to restrict the number of sexual partners to reduce the incidence of PCCL, health professionals who regularly provide care for HIV‐positive women should also recommend the VIA test.…”
Section: Discussionmentioning
confidence: 99%